A performance-based approach to evacuation analysis: A case study of two shopping centres - Normala binti Sulliaman (Kulliyyah of Architecture, Environmental and Design, International Islamic University Malaysia, 2011)
This study is focused on exploring the capabilities and output of computer modeling in two shopping centres in Malaysia. In this study, the software SIMULEX is used to analyse Total Evacuation Time (TET) and occupant behaviour when the building is evacuated using the performance-based approach. So far, this software has not been used in Malaysia. In presence of new and complex projects, the prescriptive code used for the design of a performance of egress-system is not longer appropriate. Therefore, computer modeling based on performance-based approach is used to design an emergency safety for occupant. However, due to time constraint, this study only focused on Malaysia standard prescriptive code Uniform Building by Law (UBBL) 1984 using performance based approach by computer modeling software. Due to the limitations of study, the comparison between a real life fire drill and simulation could not be carried out and could be done for future work.